Development of Android-Based Expert System to Diagnose Faults on Computer Devices - Nafis Akhsan (Institute of Computer Science (IOCS), 2020)
Repairing damage to computer equipment can be difficult if the exact cause of the problem is not known. Therefore, it is necessary to diagnose the cause of the damage first before carrying out repairs. Diagnosis of the cause of the damage can be done using the help of an expert system application. By using an expert system application, one can easily analyze the cause of the damage like when consulting with an expert. In addition, with the application of an expert system, one can also learn to find out the patterns or paths of diagnosing a problem on the computer. Therefore, this study aims to develop an expert system application to perform diagnostics to repair damage to a computer or PC. The type of research conducted is Research and Development (R&D). The R&D process uses a linear or waterfall sequential method which includes the stages of needs analysis, design, implementation, and testing. The expert system application is built to work on an android smartphone device. In order to produce a good application, this study uses the ISO 9126 standard as a standard for the level of application feasibility. The ISO 9126 standard used covers aspects of functionality, reliability, maintainability, portability, and usability. In order to produce a good application, this study uses the ISO 9126 standard as a standard for the level of application feasibility. The ISO 9126 standard used covers aspects of functionality, reliability, maintainability, portability, and usability. In order to produce a good application, this study uses the ISO 9126 standard as a standard for the level of application feasibility. The ISO 9126 standard used covers aspects of functionality, reliability, maintainability, portability, and usability.